2014
DOI: 10.1016/j.cell.2014.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Multiplatform Analysis of 12 Cancer Types Reveals Molecular Classification within and across Tissues of Origin

Abstract: Recent genomic analyses of pathologically-defined tumor types identify “within-a-tissue” disease subtypes. However, the extent to which genomic signatures are shared across tissues is still unclear. We performed an integrative analysis using five genome-wide platforms and one proteomic platform on 3,527 specimens from 12 cancer types, revealing a unified classification into 11 major subtypes. Five subtypes were nearly identical to their tissue-of-origin counterparts, but several distinct cancer types were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

88
1,363
5
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,428 publications
(1,466 citation statements)
references
References 39 publications
88
1,363
5
10
Order By: Relevance
“…To test this directly, we performed SMS on 14 GBM tumor and seven control biospecimens. As it is difficult to obtain fresh brain tissue samples from healthy individuals, we have followed the example of the TCGA Consortium and used epilepsy samples as a control for GBM (33)(34)(35). We analyzed the RNA sequencing data by testing expression of each annotated transcript in each individual GBM sample compared against all normal samples, rather than grouping all GBM samples together.…”
Section: Resultsmentioning
confidence: 99%
“…To test this directly, we performed SMS on 14 GBM tumor and seven control biospecimens. As it is difficult to obtain fresh brain tissue samples from healthy individuals, we have followed the example of the TCGA Consortium and used epilepsy samples as a control for GBM (33)(34)(35). We analyzed the RNA sequencing data by testing expression of each annotated transcript in each individual GBM sample compared against all normal samples, rather than grouping all GBM samples together.…”
Section: Resultsmentioning
confidence: 99%
“…88 Cancer subtyping and reclassification can provide custom-designed diagnosis and guide individualized therapy. Hoadley et al, 89 for example, reclassified 3,527 cancer samples (across 12 tissue-of-origin cancer types) into 11 new types based on six kinds of multi-omic data (including exon, copy number variation, DNA methylation, miRNA, mRNA, and protein) and found that these new types are capable of providing independent prognostic power. As stated, L1 activity profiles differ among and within cancer types 32,35 and fluctuate during cancer evolution.…”
Section: Perspectives: Implications Of L1 Activity and Expression Inmentioning
confidence: 99%
“…Meanwhile, the TCGA project generated datasets for over 18 cancer types, which include gene expression, copy number alteration (CNA), DNA methylation, and somatic mutation profiles (10). All of these resources provided a rich base for cancer integrative analysis (11,12).…”
Section: Rna-binding Proteinmentioning
confidence: 99%
“…Meanwhile, the TCGA project generated datasets for over 18 cancer types, which include gene expression, copy number alteration (CNA), DNA methylation, and somatic mutation profiles (10). All of these resources provided a rich base for cancer integrative analysis (11,12).Despite the rapid growth of genomic data, the knowledge on how gene expression programs in tumors are controlled by TFs is still limited. As one challenge, the experimental condition of public ChIP-seq data, such as stem cell line, may not match the physiological condition of a specific cancer type.…”
mentioning
confidence: 99%